2019
DOI: 10.11648/j.ajns.20190802.16
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mode of Birth and Quality of Life for Women's Health During Postpartum Period

Abstract: Background: The postpartum period is attended by numerous variations in women's health. Aim: This study was aimed to assess the relationship between mode of birth and quality of life for women's health during the postpartum period. Methods: The study was conducted at the outpatient clinic of Belbeis Hospital, Belbeis City, Al Sharkia Governorate, Egypt. Study design: A descriptive study design was used in the current study. Study sample: A total of 400 women attended the outpatient clinic using a purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
3
1
0
1
Order By: Relevance
“…The study demonstrated that cesarean delivery affected the health-related quality of life postpartum women. This finding is consistent with previous studies [ 24 28 ]. The possible association may be physical functioning probably less for women who underwent cesarean section than vaginal delivery.…”
Section: Discussionsupporting
confidence: 94%
“…The study demonstrated that cesarean delivery affected the health-related quality of life postpartum women. This finding is consistent with previous studies [ 24 28 ]. The possible association may be physical functioning probably less for women who underwent cesarean section than vaginal delivery.…”
Section: Discussionsupporting
confidence: 94%
“…In all the physical component summary domains which are physical functioning, role limitations due to physical health, bodily pain, and general health NVD groups had superior mean scores compared to the CS groups. This finding is agreeing with the Iranian study and was partly comparable to the Egyptian study which reported the same finding except in the general health domain (13,19). The explanation for the differences in the NVD and CS groups might due to the surgical procedure, and the effect of anesthesia undergone in CS groups further affect their postpartum recovery compaired to vaginal birth.…”
Section: Disscussionsupporting
confidence: 92%
“…The results of this study showed that the health-related quality of life during the postpartum period was higher in the NVD group compared to the CS group which is consistent with the study done in India and Egypt, and Nigeria (10,19,26). The results of this study demonstrate that if given the choice of birth method, women may want to consider a natural vaginal delivery due to the association with a better health-related quality of life during the postpartum period.…”
Section: Disscussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pesquisa realizada no Egito, com 400 mulheres no período pós-parto, mostrou que o parto vaginal influenciou de forma positiva a QV dessas puérperas 5 . No Canadá, estudo realizado com 3355 puérperas mostrou que mulheres com concepção espontânea tiveram maiores escores de QV no domínio físico do que aquelas com concepção assistida.…”
Section: Introductionunclassified